FENOMENA BERBURU TAKJIL DALAM MENINGKATKAN TOLERANSI DI INDONESIA SEBAGAI IMPLEMENTASI NILAI PANCASILA - Febriyanti, Olivia Dwi; Hasasah, Nadiatul; Rahmadhanti, Karina Oktavia; Puspita, Ari Metalin Ika (Civic Society Research and Education: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2024)
Indonesia is a country that has many tribes, races, and religions. However, the existence of many of these differences makes Indonesia a country rich in diversity. The phenomenon that has emerged recently is the "war takjil" that occurs between Muslims and non-Muslims. The phenomenon of "takjil" itself is a practice that has been carried out for a long time in Indonesia, especially during the fasting month. Takjil is a traditional practice that strengthens social ties and brings people closer, a practice that has been carried out for a long time in Indonesia, especially during the fasting month. In the holy month of Ramadan, takjil has its own meaning because it not only marks the end of fasting, but also fosters a sense of togetherness and unity among people from various backgrounds. This study discusses the phenomenon of hunting takjil in Ramadan with the object of users of the Tiktok and YouTube platforms that are specifically for people of religions other than Islam. The purpose of this study is to encourage the community to strengthen tolerance, social relations between religious communities can be well established and other good influences that affect the form of implementation in values in the form of pancasila. The method used in this study is a descriptive qualitative research method, in the form of quotes in narratives available in data in the form of videos from the Tiktok and YouTube platforms. The results showed that many religious people other than Islam also hunt takjil in Ramadan so as to make the interaction that occurs between communities harmonious and full of positive energy. It is also well rated by some religious leaders because it is considered to bring happiness and beauty.